Fintech, Financial Knowledge and Performance: Factors That Support The Sustainability of MSMEs - Nugraheni Peni; Salpiah Neng Sri Yayu; Hamzah Noradiva (SHS Web of Conferences)
The use of technology in business can affect the company’s performance to survive in the long term. This study aims to determine the influence of Financial Technology and Financial Knowledge on the performance of MSMEs. Financial technology is measured using two proxies, namely automatization and alternative payment methods (APMs). This study uses primary data based on questionnaires distributed to MSME managers and owners in Kebumen District, Central Java, Indonesia using the purposive sampling method. Hypothesis testing uses SEM-PLS analysis with the SmartPLS application version 4.0. The statistical results show that APMs and financial knowledge have a positive effect on the performance, while automation have no effect on the performance of MSMEs. The results of this study are expected to encourage MSME management to improve their capabilities related to financial technology and financial knowledge to support business sustainability.